Curtin’s Circus : the Prime Minister and Canberra news correspondents, 1941-1945 - Coatney, Caryn (Curtin University, 2011)
While the Australian wartime Prime Minister, John Curtin, has been the subject of intensive biographical and historical material, particularly during World War II, very few publications have focused on his relationships with journalists. Certainly, there is a distinct absence of a comprehensive study of his mass media strategies that would give us a detailed insight into his leadership in a critical period. Major forces converged with the commencement of another global war, the rapid expansion of relatively new radio and film industries, along with the appointment as prime minister of a skilful Labor communicator, well-known for his passionately anti-conscription views during World War I.This thesis investigates Curtin’s success in persuading the predominantly conservative news media to promote his wartime views. First, it identifies the prime minister’s mass media strategies to influence the Canberra Parliamentary Press Gallery journalists and their editors to accept his wartime policies and portray them positively in the media.The thesis argues that Curtin revealed a genius for initiating, developing and overseeing mass media strategies that made the best use of the latest technology to persuade journalists to communicate his government’s policies. In doing so, he extended the Australian public sphere, and his impact on political communications remains evident today. Curtin also bestowed a permanent legacy to benefit the parliamentary press gallery, contributing to our understanding of contemporary political journalism.